2020
DOI: 10.1016/j.fertnstert.2019.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endometrial prostanoid profiles in three infertile subgroups: the missing part of receptivity?

Abstract: Objective: To study the prostanoid profile of the endometria of patients with recurrent implantation failure (RIF), unexplained infertility (UIF), and recurrent miscarriages (RM), and to compare them with the endometria of healthy fertile controls. Design: Prospective cohort study. Setting: University hospital. Patient(s): Fifteen patients with RIF, 18 patients with UIF, 16 patients with RM, and 23 fertile controls were recruited. Intervention(s): Endometrial samples were taken during the window of implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Furthermore, platelet and endothelial cell adhesion molecule 1 (PECAM1) and transforming growth factor β1 (TGF-β1) were also significantly reduced in RIF (Guo et al, 2018). Apart from altered implantation markers, it has been previously shown that prostaglandins' synthesis is deranged in case of RIF, implying a defective endometrial inflammation in favor of implantation failure (Achache et al, 2010;Demiral Keleş et al, 2020). Finally studies evaluating metabolomics (RoyChoudhury et al, 2016) and microRNAs (Shi et al, 2017) have shown that RIF may be featured by a significant different profile that could be associated with poor reproductive outcome.…”
Section: Non-immunological Disordersmentioning
confidence: 99%
“…Furthermore, platelet and endothelial cell adhesion molecule 1 (PECAM1) and transforming growth factor β1 (TGF-β1) were also significantly reduced in RIF (Guo et al, 2018). Apart from altered implantation markers, it has been previously shown that prostaglandins' synthesis is deranged in case of RIF, implying a defective endometrial inflammation in favor of implantation failure (Achache et al, 2010;Demiral Keleş et al, 2020). Finally studies evaluating metabolomics (RoyChoudhury et al, 2016) and microRNAs (Shi et al, 2017) have shown that RIF may be featured by a significant different profile that could be associated with poor reproductive outcome.…”
Section: Non-immunological Disordersmentioning
confidence: 99%
“…Arachidonic acid-derived prostaglandins have also been shown to play a regulatory role in embryo implantation and uterine receptivity via angiogenesis stimulation and myometrium relaxation and contraction [ 29 ]. PGE 2 and PGF 2α can be involved in maternal–embryonal crosstalk and successful implantation in both animal [ 34 , 35 , 36 , 37 ] and human studies [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…AA is, in turn, metabolized by cyclooxygenases (COXs), lipoxygenases (LOXs) and nitric oxide synthase (NO S ), giving rise to different oxidation products such as PGs, thromboxanes (TXs), leukotrienes (LTs) and lipoxins (LXs). Cytokines trigger the up-regulation of COX-2 expression; as result, the COX-2-dependent prostaglandin E2 (PGE 2 ) biosynthesis is higher in the peritoneal fluid of EMS patients compared to normal endometrium [ 16 , 18 , 19 , 20 , 21 ]. This inflamed micro-environment strongly sustains the proliferation and invasion of the endometrium epithelial and stromal cells, reducing apoptosis and enhancing angiogenesis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%